Use of Ultrasound Imaging in retraining the plevic-floor muscles of a woman postpartum with urinary incontinence - Kołodyńska, Gabriela; Andrzejewski, Waldemar (Journal of Education, Health and Sport, 2019)
Pregnancy and childbirth are a recognized risk factor for urinary incontinence in women at a young age. It is suggested that the vaginal delivery is the main factor of this phenomenon due to mechanical damage of the muscle tissue and nerve. Nevertheless, the mere pregnancy can cause hormonal changes, mechanical, leading to urinary incontinence. Postnatal Physiotherapy in Poland is unfortunately often overlooked and underdeveloped area. More and more frequently in the treatment of urinary incontinence treatment uses ultrasound imaging. Using the image on ultrasound in real time, you can watch the work of the muscles. pelvic ultrasound apparatus using a physical therapist teach the patient the specific activation of muscle or group of muscles. Sonofeedback teaching allows motor traffic. This method allows precise identification and appropriate work isolated muscles. An extremely important area of application where there is sonofeedback treatment of patients with urinary incontinence.